Winging it [Free Flight, air traffic control]. - Bretz, E.A (IEEE spectrum)
The FAA believes that the solution to delayed flights is beginning to shape up. The agency is optimistic that its modernization plan and efforts to implement a program called Free Flight will go a long way toward solving the problem. Simply put, Free Flight opens the skies to air traffic, removing many of the enforced air routes that planes were required to follow. The program calls for air traffic controllers to continue to supervise flight operations and monitor safety measures. But air traffic controllers, still using equipment that is decades old and breaks down frequently, are wary of FAA promises. Planned software upgrades are being installed to improve air traffic control systems. Upgrades in about half of the 20 en route centers in the United States, which handle aircraft at higher, cruising altitudes, have gone pretty smoothly, but there have been some mishaps. What will help the situation, and is already being tested in limited circumstances in certain air traffic facilities as prototypes, is better technology that will give controllers more reliable displays, computer systems, decision-support tools, and data-all goals of Free Flight, or at least of Phase I of the program